TREATMENT OF POLYPOID RHINOSINUSITIS IN MODERN TIMES - Abdullaev U. P.; Akhundjanov N. A.; Khodjanov Sh. K.; Saidakhmedova Sh. S.; Shaumarov A. Z. (Web of Journals Publishing, 2024)
Treatment of polyposis rhinosinusitis is currently an urgent problem of modern otorhinolaryngology. A significant increase in the prevalence of the disease with polypous rhinosinusitis (from 5 to 20%) and a high frequency of relapses are due to insufficiently studied pathogenetic mechanisms for the development of the polypous process and the lack of effective methods of treatment. The combination of this disease with bronchial asthma, the asthmatic triad and the addition of a purulent process significantly complicate the course and treatment of patients with polypous rhinosinusitis. In accordance with the multifactorial theory, the development of polyposis rhinosinusitis occurs as a result of mechanical, physical factors, as well as the penetration of microbial, fungal and viral agents on the surface of the nasal mucosa. This leads to the activation of the mechanisms of local immunity, which is a whole complex of specific and non-specific reactions that provide the barrier function of the mucous membrane. Long-term exposure to various agents leads to a decrease in the activity of the protective barrier of the nasal mucosa and stimulates the development of an infection-dependent allergic process. The latter is accompanied by a violation of immune homeostasis in the form of secondary immunodeficiency, the formation of persistent immune eosinophilic inflammation, leading to remodeling of the nasal mucosa and the development of polypous rhinosinusitis.
Keywords: polyps, nasal cavity, rhinosinusitis, allergy, bronchial asthma.